Ta’lim Maharah Al-Kalam Fi Al-Ma’had Al-Salafi Bayna Al-Musykilah Wa Al-Hulul - -, Ach. Fadoli (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
Islamic boarding schools are educational foundations that prioritize the study of classical books in their learning, learning Arabic at Islamic boarding schools prioritizes the goal of understanding Arabic grammar in order to create students who are able to read classic books well, learning there does not pay too much attention to aspects other language skills such as speaking skills. This article aims to describe learning Arabic speaking skills at Islamic boarding schools, the problems encountered and the solutions provided, this research is a qualitative research with a case study type. The results of this study indicate that the learning of Arabic speaking skills in Islamic boarding schools is classified as stagnant, while most of the problems encountered are the lack of clarity in the applied curriculum which includes learning methods, learning media, and the material being taught. The solution offered is to provide innovation in the methods used, such as implementing language games in learning.